EVALUASI PROGRAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) AKSI DETEKTIF LINGKUNGAN DI KELAS 4 SDN CILANGKAP - Lutfiah Mualifa; Prayuningtyas Angger Wardhani; Indah Wardatussa'idah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The Pancasila Student Profile Strengthening Project (P5) environmental detective action focuses on the extent of success of this program in teaching Pancasila values ​​and increasing environmental awareness among students. This research aims to evaluate the implementation of the Environmental Detective Action for the Pancasila Student Profile Program (P5) in Class IV of SDN Cilangkap. The research method used is qualitative with the Context, Inputs, Process, Product (CIPP) evaluation model which combines analysis of the program context, input provided, implementation process and results obtained. Data collection was carried out through observation, interviews and analysis of documents related to the program. The research results show that overall program implementation has been good and reached optimal levels. Aspects of the context, input, process and results of the program are considered very good.